IMPLEMENTATION OF VIBRATION AND WAVES MODULE BASED ON STEM EDUCATION TO IMPROVE HIGHER-ORDER THINKING ABILITY VIEWED FROM STUDENT'S SELF CONFIDENCE - Nurhayati, Nurhayati; Wahyudi, Wahyudi; Saputri, Dwi Fajar (Jurnal Pendidikan Matematika dan IPA, 2022)
This study aims to determine (1) the effect of implementing STEM-based modules on students' higher order thinking skills; and (2) the effect of self confidence on students' higher order thinking skills. This study used an experimental method with a one way ANOVA research design. The research sample was 18 students in one class and attended vibration and wave courses. The instrument used to measure students' high-order thinking skills in the form of HOTS test questions in the form of essays totaling 10 questions that have high valid and reliable criteria and a closed questionnaire with a Likert scale to measure student self-confidence. The research data were analyzed statistically which included the N-Gain test, analysis prerequisite test and hypothesis testing. The results showed that significantly, learning using STEM-based modules had an effect on students' higher order thinking skills. The increase in students' higher order thinking skills is higher for the level of creating when compared to the level of analyzing and evaluating. Meanwhile, there is no significant effect of self-confidence on students' higher order thinking abilities.